Impact of Rapid Molecular Respiratory Virus Testing on Real-Time Decision Making in a Pediatric Emergency Department - Rogan, Daniel T. (J Mol Diagn, 2017)
Acute respiratory illnesses (ARIs) are usually viral [influenza, respiratory syncytial virus (RSV)] and account for 25% of emergency department (ED) peak-season visits. Laboratory PCR testing is accurate albeit slow, whereas rapid antigen testing is inaccurate. We determined the impact of bedside PCR (molecular point-of-care test; mPOCT) on pediatric ARI management. This was a prospective cohort study of consecutive pediatric patients with ED-ordered respiratory PCR test, enrolled over 9 weeks during peak flu season. On ordering, ED physicians were interviewed to ascertain real-time plans if given immediate influenza/RSV PCR results for the current patient. Two groups were compared: actual management and management adjusted for mPOCT results. We compared ED length of stay (LOS), tests ordered, and antibiotic/antiviral ordering. One-hundred thirty-six respiratory PCR panels were ordered, 71 by admitting team, 61 for ED management. Of 61 ED-initiated tests, physicians indicated in 39 cases (64%) they would change patient management were bedside viral results available. Physicians would have decreased ED LOS by 33 minutes, ordered fewer tests (18%; P < 0.001) with average patient charge savings of $669, fewer antibiotics among discharged patients (17%; P = 0.043), and increased appropriate antiviral use (13%; P = 0.023). Rapid bedside ARI mPOCT PCR has the potential to decrease ED LOS, reduce diagnostic tests and patient charges, and increase appropriate use of antibiotics and antiviral agents.